Crescimento e produção de Tectona grandis L.f em um plantio no município de Alta Floresta – MT - Silva, Fabricia Rodrigues da (2012)
This study aimed to evaluate the growing and production of species by the behavior of the variables diameter, high and volume along the period from 1998 to 2011; to classificate the local productivity by apllying the medium curve method in the reference age of 84 months; and to adjust a growing and production model in a plantation of teak (Tectona grandis) in Alta Floresta city – MT. They were used data from permanent plots, scaling and complete stem analysis. They were adjusted hipsometric and volumetric models to estimate the growing of dendometric variables, to elaborate site index curves and to determine the total production in volume and basal area by applying Beck and Della-Bianca's model. As final results, there are the Prodan equation, to explain the ratio between high and diameter; Schumacher-Hall's equation, which was selected to estimate the volume; and Shumacher's model, which presented the best performance to generate the classification curves for productivity. Anamorphism test demonstrated that the data basis follow an anamorphic pattern. After the adjustment and accuracy analysis, Beck and Della-Bianca's model was efficient in projecting the variables basal area and population volume. Considering the results for growing and production analysis, it can be deduced that the studied species has increments which are compatible when compared to other regions, allowing to coclude that its development is fully viable to this region.